COMPARATIVE ANALYSES OF SEX‐RATIO VARIATION IN DIOECIOUS FLOWERING PLANTS. (20th December 2012) - Field, David L.; Pickup, Melinda; Barrett, Spencer C. H.
Abstract : Dioecious plant species commonly exhibit deviations from the equilibrium expectation of 1:1 sex ratio, but the mechanisms governing this variation are poorly understood. Here, we use comparative analyses of 243 species, representing 123 genera and 61 families to investigate ecological and genetic correlates of variation in the operational (flowering) sex ratio. After controlling for phylogenetic nonindependence, we examined the influence of growth form, clonality, fleshy fruits, pollen and seed dispersal vector, and the possession of sex chromosomes on sex‐ratio variation. Male‐biased flowering sex ratios were twice as common as female‐biased ratios. Male bias was associated with long‐lived growth forms (e.g., trees) and biotic seed dispersal and fleshy fruits, whereas female bias was associated with clonality, especially for herbaceous species, and abiotic pollen dispersal. Female bias occurred in species with sex chromosomes and there was some evidence for a greater degree of bias in those with heteromorphic sex chromosomes. Although the role of interactions among these correlates require further study, our results indicate that sex‐based differences in costs of reproduction, pollen and seed dispersal mechanisms and sex chromosomes can each play important roles in affecting flowering sex ratios in dioecious plants.